Review: Moulton and Geden. Concordance to the Greek New Testament. Sixth Edition Fully revised - Hooker, Morna Dorothy (The journal of theological studies, 2004)
Moulton and Geden. Concordance to the Greek New Testament. Sixth Edition Fully revised. I. Howard Marshall Pp. xxi+1121 Edinburgh and New York T. & T. Clark 2002 0 567 08571 6 £ 60.